Bangladesh: Country brief - HarvestPlus (International Food Policy Research Institute, 2015)
HarvestPlus improves nutrition and public health in Bangladesh by promoting rice that provides more zinc in the diet. We work with almost 40 partners drawn from government, business, and civil society.